Temperature thresholds of ecosystem respiration at a global scale - Johnston, Alice S. A.; Meade, Andrew; Ardö, Jonas; Arriga, Nicola; Black, Andy; Blanken, Peter D.; Bonal, Damien; Brümmer, Christian; Cescatti, Alessandro; Dušek, Jiří; Graf, Alexander; Gioli, Beniamino; et al. (Nature Publishing Group, 2021)
Ecosystem respiration is a major component of the global terrestrial carbon cycle and is strongly influenced by temperature. The global extent of the temperature–ecosystem respiration relationship, however, has not been fully explored. Here, we test linear and threshold models of ecosystem respiration across 210 globally distributed eddy covariance sites over an extensive temperature range. We find thresholds to the global temperature–ecosystem respiration relationship at high and low air temperatures and mid soil temperatures, which represent transitions in the temperature dependence and sensitivity of ecosystem respiration. Annual ecosystem respiration rates show a markedly reduced temperature dependence and sensitivity compared to half-hourly rates, and a single mid-temperature threshold for both air and soil temperature. Our study indicates a distinction in the influence of environmental factors, including temperature, on ecosystem respiration between latitudinal and climate gradients at short (half-hourly) and long (annual) timescales. Such climatological differences in the temperature sensitivity of ecosystem respiration have important consequences for the terrestrial net carbon sink under ongoing climate change.
Keywords: Ecosystem ecology